2021
DOI: 10.3390/su131910932
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Oscillating Surge Wave Energy Converter Performance: A Case Study for Southern Coasts of the Caspian Sea

Abstract: The search for renewable energy supplies for today’s global energy demand, particularly ocean wave energy for coastal areas, has become undeniably widespread in the last two decades. The Caspian Sea represents an immense opportunity for using ocean renewable energy, especially considering its long shoreline. In this study, the locations with maximum potential wave energy were chosen in the central, eastern, and western zones of the Caspian Sea’s southern coasts. Accordingly, the wave and bathymetric data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The study uses the oscillating surge wave energy converters flap geometric dimensions as the data to simulate in the MATLAB software. The results found that the Nowshahr port has more potential than the Anzali and Amirabad ports, under the condition's absorbed power of 16.7 kW/m (Capture factor = 63%) at these sites [11]. The methods in references above use the different models and study at the different environment sites.…”
Section: Fig1 Flowchart Of Research Methodologymentioning
confidence: 99%
“…The study uses the oscillating surge wave energy converters flap geometric dimensions as the data to simulate in the MATLAB software. The results found that the Nowshahr port has more potential than the Anzali and Amirabad ports, under the condition's absorbed power of 16.7 kW/m (Capture factor = 63%) at these sites [11]. The methods in references above use the different models and study at the different environment sites.…”
Section: Fig1 Flowchart Of Research Methodologymentioning
confidence: 99%
“…Eight Persian Gulf locations based on a 20-year wave horizon were assessed. Also in 2020, Amini et al assessed the deployment of an oscillating flap-type WEC in the Caspian Sea [99]. They used SWAN to obtain input waves, ABAQUS to find the optimal flap width and height at each site, and compare device performance to evaluate the optimal site for wave energy production.…”
Section: Novel Applicationsmentioning
confidence: 99%
“…However, waves in real seas are irregular as a result of their random behavior. Here, an irregular wave is treated as the superposition of regular-wave components with discrete wave frequencies, the amplitude of which is determined from a wave spectrum [22,23]. One of the most commonly used wave spectrums is the Pierson-Moskowitz spectrum, which describes fully developed wind seas and can be expressed as…”
Section: The Absorbed Power Of a Point Absorbermentioning
confidence: 99%
“…In the inner loop, the buoy mass ratio mn is optimized for a given buoy geometry and sea state and under the constraint on buoy mass as defined in Equation (22). It should be clarified that, in this loop, mn is optimized based on the optimal value of cp and kc, which means that when calculating the performance of the WEC for any values of mn, both cp and kc are optimized for this specific mn accordingly.…”
Section: The Inner Loopmentioning
confidence: 99%